Dye sensitization of TiO₂ crystals and nanocrystalline films with a ruthenium based dye - Fillinger, Akiko, author; Parkinson, Bruce A., advisor (Colorado State University. Libraries, 2000)
The dye/semiconductor interface of a recently developed highly efficient (overall conversion efficiency > 13 %) dye sensitized nanocrystalline TiO2 solar cell was investigated. First, the adsorption and desorption rates of the dye (cis-di(thiocyanato)bis(2.2'-bipyridyl-4.4'-dicarboxylate)ruthenium(II):N3), and the relationship between the dye coverage and the photon-to-current conversion efficiencies were examined for nanocrystalline TiO2 films. A two-step dye adsorption mechanism was postulated where initial binding of N3 is through one carboxyl group, with subsequent binding of two or more carboxyl groups. The photon-to-current conversion efficiencies were found to increase abruptly at a coverage of about 0.3 monolayers. To explain the non-linear increases in the conversion efficiencies, a hole-hopping mechanism was proposed. At greater than 30 % coverage, hole transfer between adjacent N3 molecules becomes possible and facilitates the regeneration of the oxidize d N3 by the redox species (I-) in the matrix of the nanoporous structure. Natural anatase crystals were also investigated as substrates for dye sensitization by N3 to circumvent the complexity of the nanoporous structure of the nanocrystalline TiO2 films. A crystal face dependence of the sensitization yield was observed and explained with the variation in the distances between the Ti binding sites by different crystal faces. The dye sensitized photocurrents with the natural anatase crystals had millisecond rise times. The rise time decreased with greater light intensity and greater dye coverage, suggesting that trapping and detrapping of injected electrons at traps in the crystals is involved in the electron transport in the natural anatase crystals. The absorbed photon to current efficiency of the nanocrystalline films was calculated to be approximately three to seven times greater than that of the single crystals, indicating more recombination in the single crystals. Finally, the surface morphologies of natural and synthetic TiO2 crystals were investigated with scanning electron microscopy and atomic force microscopy. Several surface treatments were attempted to obtain flat terraced surfaces suitable for imaging the adsorbed N3.
Dye sensitization of titanium dioxide crystals and nanocrystalline films with a ruthenium based dye
Keywords: analytical chemistry; materials science; condensation; energy; condensed matter physics